Applying social computing to generate sound clouds. (January 2017) - Navarro-Cáceres, María; Bajo, Javier; Corchado, Juan Manuel
Abstract: Human beings make decisions on a daily basis according to their social environment. Social information given by such social contexts provides the basis for inferences, planning and coordination of any activity. Social machines aim to incorporate this concept of social nature and make it possible to design digital systems that make information visible to the users. This paper presents a social machine implemented as a VO where humans and machines collaborate in a creative process to transform a picture into a musical sound cloud. The VO is implemented by a MAS, and defines specialized roles for extracting sounds from the color pixels of the image. As a part of the social machine and in order to demonstrate the viability of the system, the prototype built from this model is evaluated by experts who rate the sounds produced following consonance criteria.